Tyrosine kinase inhibitors for the treatment of rheumatoid arthritis: phase I to Ⅱ clinical trials. (2nd December 2019) - Wu, Jing; Zhu, Zhaohua; Yu, Qinghong; Ding, Changhai
ABSTRACT: Introduction : Rheumatoid arthritis (RA) is a chronic, refractory disorder caused by autoimmunity in the synovial joints. Disease-modifying anti-rheumatic drugs (DMARDs) and biologicals offer remission in only two-thirds of RA patients within 3 months, hence new therapeutic approaches are necessary. Tyrosine kinase inhibitors (TKIs) are newly developed small molecule drugs which have demonstrated encouraging results in this disease. Areas covered : The key findings from phase I and II clinical trials that have investigated the use of novel TKIs in the treatment of RA are discussed. We examined the literature published between January 2014 to January 2019 using electronic databases including PubMed, Web of Science, Medline, Embase, and Google Scholar. Additional information about phase I and II trials on the ClinicalTrial.gov website up to January 2019 was also retrieved. Expert opinion : JAK inhibitors are promising drugs with sound efficacy and acceptable safety and may be beneficial to patients who do not respond to DMARDs and biologicals. The response rates among RA patients to TKIs are diverse; genetic and environmental factors may be involved in the varying responses which are closely related to the pathogenesis of RA. Future studies may reveal the underlying mechanisms of resistance and non-response.